Economic aspects of oil conservation regulation - Lovejoy, Wallace F.; Homan, Paul T.; Resources for the Future (Baltimore : Published for Resources for the Future by Johns Hopkins Press, 1967)
This book traces the history and implementation of regulation programs for state crude oil production.
Include index
kjo 14/01/2019
Loans
Keywords: Petroleum industry and trade; Petroleum law and legislation; Petroleum conservation